2016
DOI: 10.1038/ni.3644
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase UTX regulates the lineage-specific epigenetic program of invariant natural killer T cells

Abstract: Invariant natural killer T (iNKT) cells are innate-like lymphocytes that protect against infection, autoimmune disease and cancer. However, little is known about epigenetic regulation of iNKT cell development. Here, we show that the H3K27me3 histone demethylase UTX is an essential cell-intrinsic factor that controls an iNKT lineage-specific gene expression program and epigenetic landscape in a demethylase activity dependent manner. UTX-deficient iNKT cells exhibited impaired expression of iNKT signature genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 61 publications
4
55
0
Order By: Relevance
“…UTX is the major demethylase of H3K27me3 (15), and a previous study has shown that loss of UTX results in deregulation of the cell cycle via RB-dependent pathways (36). Moreover, UTX has been reported to regulate the development of invariant natural killer T cells via the epigenetic program (37). Interestingly, UTX somatic mutations are frequently detected in various epithelial cancers, including multiple myeloma, esophageal squamous cell carcinoma, and lung cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…UTX is the major demethylase of H3K27me3 (15), and a previous study has shown that loss of UTX results in deregulation of the cell cycle via RB-dependent pathways (36). Moreover, UTX has been reported to regulate the development of invariant natural killer T cells via the epigenetic program (37). Interestingly, UTX somatic mutations are frequently detected in various epithelial cancers, including multiple myeloma, esophageal squamous cell carcinoma, and lung cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Cis elements recruit the H3K27 demethylase KDM6A/ UTX Our findings collectively suggest that type 1A domains are intrinsically predisposed to acquiring H3K27me3, with deposition and erasure occurring dynamically. One possible way for enhancers to offset H3K27me3 spread is to recruit a demethylase such as KDM6A/UTX, which limits H3K27me3 accumulation at promoters (Agger et al 2007;Arcipowski et al 2016) and is reported to bind certain heart-specific and T-cell-specific enhancers (Lee et al 2012;Beyaz et al 2017). To test whether intestinal CDX2-dependent enhancers recruit KDM6A to avoid H3K27me3 accumulation, we first confirmed that the KDM6A antibody recognizes a single protein of the expected mass by immunoblotting ( Supplemental Fig.…”
Section: Tf-dependent Exclusion Of H3k27me3 From Enhancers In Anothermentioning
confidence: 97%
“…The pharmacological inhibition of BRD4 by JQ1 inhibited a broad range of TNF-α-responsive genes, suggesting the important role of SEs in the inflammatory response of ECs (Brown et al, 2014). More recently, Beyaz et al showed that UTX facilitates the accessibility of SEs that establish the cell identity of invariant natural killer T cells, in accordance with low levels of H3K27me3 (Beyaz et al, 2017). This study raised the possibility that the erasure of repressive histone marks by histone demethylases correlates with the formation of SEs and the activation of associated genes; however, these points have not been addressed during the early inflammatory responses.…”
Section: Inflammatory Responses Are Controlled By Master Transcriptiomentioning
confidence: 99%